Paving slabs and curbs change in the composition of concrete - Zhumin, Абылайхан (Рroblems of engineering and professional education, 2023)
The article is devoted to a deep analysis of the work done on the creation of modern paving slabs and curbs. The analysis of scientific researches on increase of physical and chemical characteristics of a material is given. The author focuses on the effect of hyperplasticizers on the physical characteristics of the material. This direction is supplemented by the same consideration of nanodispersed concrete systems.